Linking Spending and Quality Indicators to Measure Value and Efficiency in Health Care. (August 2017) - Ryan, Andrew M.; Tompkins, Christopher P.; Markovitz, Adam A.; Burstin, Helen R.
Policy makers and stakeholders have reached a consensus that both quality and spending or resource use indicators should be jointly measured and prioritized to meet the objectives of our health system. However, the relative merits of alternative approaches that combine quality and spending indicators are not well understood. We conducted a literature review to identify different approaches that combine indicators of quality and spending measures to profile provider efficiency in the context of specific applications in health care. Our investigation identified seven alternative models that are either in use or have been proposed to evaluate provider efficiency. We then used publicly available data to profile hospitals using these approaches. Profiles of hospital efficiency using alternative models yielded wide variation in performance, underscoring the importance of model selection. By identifying the current efficiency models and evaluating their trade-offs within specific programmatic contexts, our analysis informs stakeholder and policy maker decisions about how to link quality and spending indicators when measuring efficiency in health care.